Approximation of $\overline ψ$-Integrals of Periodic Functions by de la Vallée-Poussin Sums (Low Smoothness) - Rukasov, V. I.; Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the asymptotic behavior of the upper bounds of deviations of linear means of Fourier series from the classes $C_{∞} ^{ψ}$. In particular, we obtain asymptotic equalities that give a solution of the Kolmogorov – Nikol'skii problem for the de la Vallée-Poussin sums on the classes $C_{∞} ^{ψ}$.